Does green finance promote the improvement of regional eco-efficiency? Direct and spillover effects - Zhang, Yuze; Zhang, Jisong; Liu, Yuqing (Frontiers in Environmental Science, 2024)
IntroductionGreen finance plays a pivotal role in advancing China’s ecological civilization construction and achieving sustainable economic and social development.MethodsUsing panel data from 30 provinces in China from 2009 to 2021, this study applies the entropy weighting method and the super-efficiency slack-based measure (Super-SBM) model to assess the levels of green finance and eco-efficiency in each province. Employing spatial statistical methods such as the spatial standard deviation ellipse (SSDE) and the spatial Markov chain, the study reveals the spatiotemporal evolution characteristics of green finance and eco-efficiency. Additionally, the spatial Durbin model is used to analyze the direct effects, spatial spillover effects, and spatial heterogeneity features of green finance on regional eco-efficiency.ResultsThe results show that (1) From 2009 to 2021, green finance and regional eco-efficiency levels exhibited an overall upward trend, though with notable spatiotemporal differences. (2) The direct and spatial spillover effects of green finance on regional eco-efficiency followed a notable inverted U–shaped relationship. However, in most provinces, green finance levels had not yet reached the turning point during the study period, and the impact of green finance on regional eco-efficiency remained largely positive. (3) The effects of green finance on regional eco-efficiency showed considerable structural differences due to regional heterogeneity, with the strongest effects observed in the Eastern regions.DiscussionThis study provides policymakers with strategies to enhance regional eco-efficiency through the development of green finance, offering valuable insights for promoting ecological civilization construction and achieving sustainable development.